Developing 'Pizza for Circles' media: A preliminary study on enhancing seventh-grade students' conceptual understanding - Thevando Inteng Sukendro; Putri Fitria Hermalina; Karunia Karunia; M Aziz Alhakim R; Meryansumayeka Meryansumayeka; Zulkardi Zulkardi; Budi Mulyono; Hapizah Hapizah; Elsa Susanti (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aimed to develop a mathematics learning tool called “Pizza for Circles” to help students better understand the concept of circles. Students often memorize formulas without grasping the underlying concepts, particularly the area and circumference of a circle, which is the problem this study addresses. A research and development method was used to create manipulative and visual media supported by a website as a learning aid. This media presents a circle as a pizza divided into eight slices, illustrating the relationships among its components. A one-group pretest–posttest design was applied to a small group of three seventh-grade students. The media was validated by two experts, achieving 98.75% for material content and 86.4% for media design, both of which fall in the highly valid category. A small-group trial with the same three students showed a descriptive increase in the mean score from 2.0 to 5.83 out of 10 after a single-session intervention, corresponding to a normalised gain of 0.48 (medium category). Because the sample was very small, the results were not tested inferentially; nevertheless, they indicated an improvement in students’ understanding, as evidenced by higher post-test scores than pre-test scores. These results suggest that the “Pizza for Circles” media can aid in the initial understanding of circle concepts through a visual and manipulative approach. Further research with a larger sample and a longer learning period is nevertheless required before any claim of effectiveness can be made.